2018
DOI: 10.1016/j.cej.2017.10.119
|View full text |Cite
|
Sign up to set email alerts
|

Development of an ASM2d-N2O model to describe nitrous oxide emissions in municipal WWTPs under dynamic conditions

Abstract: Nitrous oxide (N 2 O), a significant contributor to the greenhouse effect, is generated during the biological nutrient removal in wastewater treatment plants (WWTPs). Developing mathematical models estimating the N 2 O dynamics under changing operational conditions (e.g. dissolved oxygen, DO) is essential to design mitigation strategies. Based on the activated sludge models (ASM) structure, this work presents an ASM2d-N 2 O model including all the biological N 2 O production pathways for a municipal WWTP under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 59 publications
0
20
0
3
Order By: Relevance
“…The authors have provided guidelines for the selection of the most appropriate modelling approach under different DO and NO 2 − concentrations based on the structural assumptions of the models. The debate on the model that best describes and decouples the major N 2 O formation pathways is still ongoing with several extensions and variations of the original approaches developed recently (Ding et al, 2017;Domingo-Félez and Smets, 2016;Massara et al, 2018).…”
Section: Mechanistic Modelsmentioning
confidence: 99%
“…The authors have provided guidelines for the selection of the most appropriate modelling approach under different DO and NO 2 − concentrations based on the structural assumptions of the models. The debate on the model that best describes and decouples the major N 2 O formation pathways is still ongoing with several extensions and variations of the original approaches developed recently (Ding et al, 2017;Domingo-Félez and Smets, 2016;Massara et al, 2018).…”
Section: Mechanistic Modelsmentioning
confidence: 99%
“…Such a study, although developed on a theoretical case study, demonstrated the effectiveness of advanced mathematical modelling methods for reducing the emissions and pin down criteria for plant operational strategies. Recent studies on GHG modelling include both conventional (Massara et al, 2018) and advanced treatment systems such as membrane bioreactors (Mannina et al, 2018b). Such models are modifications of the ASM in an attempt to come up with a modelling tools for GHG emissions from WWTPs.…”
Section: Greenhouse Gases From Wastewater Treatment Plantsmentioning
confidence: 99%
“…The aerated reactors are the major contributors of OffgasN2O within the MBR plant (Ribera-Guardia et al, 2019), followed by the MBR reactor (Figure 3d). The emissions from the MBR reactor are mostly due to the stripping of N2O in gas form from its related dissolved component (Massara et al, 2018).…”
Section: <Here Figure 3>mentioning
confidence: 99%